Pengaruh Trustmarks dan Kualitas Layanan terhadap Kepercayaan Pelanggan Online Shop - Inggrid Wahyuni Sinaga; Resty Mely (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This study aims to determine the effect of trustmarks and quality of service for customer confidence. Trustmarks is a small image or logo that indicates assurance indicating that shopping at online sites secure ours. Visitors will be more likely to make a purchase if they know that their payment details secure. Quality of service is an overall impression of the consumer against the inferiority / superiority argument along with the services offered. Respondents are residents of the Perumahan Blok 2 Baloi, Batam results showed that there was a positive and significant influence variables trustmarks the trust of customers with significant value 0,009 < 0,05 and there is a positive and significant effect of the variable quality of service for customer confidence with significant value 0,000 < 0,05.